Atributos físico-hídricos e produtividade de soja e milho sob aplicação de resíduos agrícolas - Souza Júnior, Milton Rodrigues de (2015)
The application of organic residues in agricultural soils has shown satisfactory results and aiming to be a viable technology for sustainable development of the soil. However, few studies have addressed the use and application of these materials in cerrado soils where is practiced large-scale agriculture. With the hypothesis that use of organic residues in the soil can promote improvements in the physical characteristics of the soil and crop yields of soybeans and corn, this study was conducted in order to determine the physical and hydraulic characteristics and productivity of soybean and corn a Oxisol medium texture under application of agro industrial waste. The experiment was installed in Campo Verde municipality - MT, in 2012. The experimental design was a randomized block, evaluating water soil physical attributes and productivity of soybeans and corn, submitted to treatments made of sawdust waste mahogany and cedar - SPC; cane filter cake - TFC and eucalyptus tip Cavaco - CPE at doses of 6 Mg ha-1 and 18 Mg ha-1, management system with incorporation of waste and no-tillage system. The waste used in different types of soil carbon enrichment change the soil water retention capacity; The application of 18 Mg ha-1 filter cake and 18 Mg ha-1 of sawdust mahogany and cedar, in two consecutive years was enough to improve soil water retention in the layer 0.1 to 0.2 m . The yields of soybean and corn crops were affected by established treatments.